2019
DOI: 10.1177/0146167219835213
|View full text |Cite
|
Sign up to set email alerts
|

Of Nice and Mean: The Personal Relevance of Others’ Competence Drives Perceptions of Warmth

Abstract: Past research shows that when forming an impression of an interdependent person, perceivers are motivated to look for information relevant to their goals and interests. The present experiments examined what happens after this information-seeking stage and showed that the relevance of the target’s attributes for one’s goals and interests drives warmth impressions. Using both a scenario (Experiment 1) and realistic methodologies (Experiment 3), we showed that when the perceiver had to collaborate with a target, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
18
2
Order By: Relevance
“…This is also contradicts very recent behavioral findings (Carrier, Dompnier & Yzerbyt, . This is also contradicts very recent behavioral findings (Carrier, Dompnier & Yzerbyt, 2019), showing that the personal relevance of others' competence drives impressions of warmth. In the current study, the information about competence was demonstrated to be either high or low.…”
Section: Discussioncontrasting
confidence: 95%
“…This is also contradicts very recent behavioral findings (Carrier, Dompnier & Yzerbyt, . This is also contradicts very recent behavioral findings (Carrier, Dompnier & Yzerbyt, 2019), showing that the personal relevance of others' competence drives impressions of warmth. In the current study, the information about competence was demonstrated to be either high or low.…”
Section: Discussioncontrasting
confidence: 95%
“…Thus, although we consistently found a positive linear relationship between competence and valence, it is conceivable that a curvilinear or even negative relationship may emerge under different circumstances. For instance, in a competitive environment, highly intelligent individuals may be perceived as “bad” (e.g., Carrier, Dompnier, & Yzerbyt, ). Further studies may clarify how changes in the meaning of a trait modulate its perceived valence across different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine papers exclusively reporting studies with sample sizes less than 781, seven calculated a priori power analyses. Of these, four studies estimated power based on effect sizes calculated on a small pilot study ( r = .26; Wang & Ackerman, 2019), or effect sizes that were presumed to be medium to large ( r = .32; Carrier et al, 2019), medium ( r = .25; Yao & Chao, 2019), or small to medium ( r = .24; Martin et al, 2019). As these assumed interaction effect sizes imply true simple effects in an effect-present condition that is double the assumed interaction effect size (i.e., r = .40–.64), the hypothesized interaction effect sizes were overly optimistic.…”
Section: Tests Of Attenuated Interactions Are Common and Typically Unmentioning
confidence: 99%